2011
DOI: 10.1103/physrevlett.107.043003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Recapture of Electrons in Multiple Ionization of the Argon Dimer by a Strong Laser Field

Abstract: We observe multiply frustrated tunneling ionization-induced dissociation of the argon dimers by intense linearly polarized ultrashort laser pulses. By measuring the kinetic energy release and angular distribution of the Coulomb explosion of up to eightfold ionized argon dimers, we can trace the recapture of up to two electrons to Rydberg states of the highly charged compound at the end of the laser pulse. Upon dissociation of the dimer, the Rydberg electron prefers to localize at the atomic ion with the higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 24 publications
6
43
0
6
Order By: Relevance
“…Demonstrated originally in strong-field ionization of helium, Nubbemeyer et al showed that an electron wavepacket that starts to tunnel away from the core in an intense laser field, but fails to acquire sufficient drift momentum to escape the attractive potential of the remaining He + ion, can be captured into an excited Rydberg orbital of the He atom-in effect 'frustrating' the tunnel ionization process. This process must occur during the laser pulse to conserve energy and momentum, most likely during the trailing edge, as the electron is gently decelerated over many laser cycles before being pulled into orbit.The same mechanism has been observed in the dissociative ionization of a few diatomic molecules (H 2 [23], D 2 [24], O 2 [25] and Ar 2 [26][27][28]). For such molecules, following ionization, an electron that is excited to the continuum and driven by the laser field tends to be captured to a Rydberg orbital of one of the two 'Coulomb-exploding' fragment ions.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…Demonstrated originally in strong-field ionization of helium, Nubbemeyer et al showed that an electron wavepacket that starts to tunnel away from the core in an intense laser field, but fails to acquire sufficient drift momentum to escape the attractive potential of the remaining He + ion, can be captured into an excited Rydberg orbital of the He atom-in effect 'frustrating' the tunnel ionization process. This process must occur during the laser pulse to conserve energy and momentum, most likely during the trailing edge, as the electron is gently decelerated over many laser cycles before being pulled into orbit.The same mechanism has been observed in the dissociative ionization of a few diatomic molecules (H 2 [23], D 2 [24], O 2 [25] and Ar 2 [26][27][28]). For such molecules, following ionization, an electron that is excited to the continuum and driven by the laser field tends to be captured to a Rydberg orbital of one of the two 'Coulomb-exploding' fragment ions.…”
supporting
confidence: 57%
“…The same mechanism has been observed in the dissociative ionization of a few diatomic molecules (H 2 [23], D 2 [24], O 2 [25] and Ar 2 [26][27][28]). For such molecules, following ionization, an electron that is excited to the continuum and driven by the laser field tends to be captured to a Rydberg orbital of one of the two 'Coulomb-exploding' fragment ions.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…The formation of highly excited neutral fragments in linearly polarized laser fields has attracted a lot of interest in the last few years [10][11][12][13][14]. In [15] we reported a theoretical study of the mechanisms of this "frustrated"-since only one electron eventually escapes-double ionization process.…”
Section: Introductionmentioning
confidence: 99%